Gold(I) Complexes Containing Phosphanyl‐ and Arsanylborane Ligands. Issue 40 (21st June 2018) - Braese, Jens; Schinabeck, Alexander; Bodensteiner, Michael; Yersin, Hartmut; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: The structural and photophysical properties of a series of new Au I compounds have been studied. The reactions of AuCl(tht) with the phosphanyl‐ and arsanylboranes RR ′ EBH2 NMe3 (E=P, As; R=H, Ph; R′=H, Ph, t Bu) afford the complexes [AuCl(RR ′ EBH2 NMe3 )]. In the solid state, [AuCl(H2 PBH2 NMe3 )]2 (2 a ) is a dimer showing unsupported intermolecular aurophilic interactions with short Au⋅⋅⋅Au distances. In contrast, [AuCl(H2 AsBH2 NMe3 )] n (2 b ) aggregates to form 1D chains. Organic substituents on the pnictogen atoms lead to discrete molecules in [AuCl(RR ′ PBH2 NMe3 )] (2 c : R=H, R′= t Bu; 2 d : R=R′=Ph). To increase the aurophilicity, the ionic homoleptic complexes [Au(RR ′ EBH2 NMe3 )2 ][AlCl4 ] (3 a –d ) have been synthesized, for which 3 a, b form chains in the solid state and exhibit luminescence. The emissions show a drastic redshift with temperature decrease, correlating with decreasing Au⋅⋅⋅Au distances. DFT calculations provide insight into the bonding situation of the products. Abstract : A series of Au I pnictogenylborane complexes has been synthesized, including unprecedented Au I complexes with primary arsines. They show monomeric, dimeric, as well as polymeric arrangements through aurophilic interactions in the solid state. The corresponding polymers display photoluminescence in the solid state.